Vforce: An Extensible Framework for Reconfigurable Supercomputing. - Moore, Nicholas; Conti, Albert; Leeser, Miriam; King, Laurie Smith (Computer (00189162), 2007)
The article discusses applications that increase performance with reconfigurable supercomputers to achieve exponential improvements in processing speed. Reconfigurable supercomputing uses reconfigurable hardware with supercomputing architectures. Applications for reconfigurable supercomputing are often not portable across different reconfigurable computing architectures. Vforce created the Vector, Signal, and Image Processing Library (VSIPL++) which helps increase performance, code portability, and end-user productivity. Vforce's benefits and shortcomings are investigated as are some of the author's experiences with Vforce.